ANALISIS PENDIDIKAN MENENGAH DENGAN PEMBELAJARAN DIFERENSIASI DENGAN BERBAGAI PERBEDAAN DALAM GAYA KOGNITIF, SELF-EFFICACY, MOTIVASI, DAN SELF-REGULATED LEARNING BERDASARKAN PADA KONSTRUKTIVIS - Agus Qowiyuddin (Universitas Nahdlatul Ulama Pasuruan, 2023)
In differentiated learning, the role of students' cognitive style is crucial. Visual, auditory and kinesthetic students require different approaches. Self-efficacy, belief in ability, motivation and self-regulated learning also have a significant impact. Motivation is the drive, while self-regulated learning is the ability to organize the learning process. The results and discussion of this research highlight seven ways differentiated learning achieves its goals, including recognition of learning needs and styles, customization of materials, providing choice, and continuous evaluation. The research also discusses differences in cognitive style, self-efficacy, motivation, and self-regulated learning and how these concepts play a role in differentiated learning. The differentiated learning strategies discussed involve recognizing individual students, creating a positive learning environment, varying teaching methods, and utilizing technology. The role of differentiation in helping students build self-efficacy and motivation to learn is highlighted as a key contribution of differentiated learning. Despite challenges such as deep understanding of learners and preparation of differentiated materials, differentiated learning is considered to create a more positive and effective learning experience.